DAMPAK PEMBANGUNAN PLTN TERHADAP PERUBAHAN TATA RUANG KABUPATEN JEPARA - Setia Budi, Bambang (Gema Teknologi, 2010)
Bambang Setiabudi, in paper Study on effect of the NPP development toward spatial planning at District of Jepara had been done to support government policy according to governmental rule No. 5, Year of 2006 concerning National Energy Policy which nuclear energy is chosen as one of alternative energy source. The study was done by estimating growth of resident naturally with geometric method, increase of constructing labor pursuant to requirement of standard, and growth of resident as impact of economics growth and then to predict the land use change due to facilities requirement. Research result indicates that change of space pattern of non-agriculture settlement is equal to 15%. It also shows that growth of resident density rises to level of 31-45 person per ha.Keywords : spatial planning, geometric, input-output analysis, policy